Factors Influencing Vulnerable Workers in Indonesia - Bharata, Diva Adhiesti; Prestianawati, Silvi Asna (Contemporary Studies in Economic, Finance and Banking, 2026)
This article examines worker vulnerability in Indonesia through an empirical study using data from the 2024 National Labor Force Survey (Sakernas). Employing a binary logistic regression method, this research defines vulnerable workers as individuals who meet at least two of the following four criteria: (1) earning wages below the Regional Minimum Wage (UMR), (2) lacking employment, social, or health benefits, (3) working in the informal sector, and (4) having an education level below senior high school. The analysis reveals that age, migration status, job training, and technology access significantly affect the probability of an individual being classified as a vulnerable worker. Young workers, non-migrants, and those without prior job training or access to technology face a higher risk of vulnerability in the labor market. These findings empirically affirm that human capital investment is a crucial determinant of worker vulnerability. Therefore, this research recommends government policy interventions focused on the equitable distribution of digital infrastructure and the inclusivity of vocational programs. Furthermore, the public is encouraged to proactively engage in skill development to avoid the risks of employment vulnerability.